2014
DOI: 10.1371/journal.pone.0086911
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association between Insulin Receptor Substrate2 rs1805097 Polymorphism and the Risk of Colorectal and Breast Cancer: A Meta-Analysis

Abstract: BackgroundInsulin receptor substrate-2 (IRS-2), a signaling adaptor protein, was involved in two cancer-related pathways (the phosphatidylinositol 3′-kinase (PI3K) and the extracellular signal-regulated kinase (ERK) pathways). Several studies have evaluated the association between IRS2 rs1805097 (G>A) polymorphisms and the risk of colorectal and breast cancer. However, the results were inconsistent.Methodology/Principal FindingsA meta-analysis of seven published case-control studies (4 studies with 4798 cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…We believe our meta-analysis more robust than previous meta-analysis by Hu et al [20]. First, we included 2 extra studies and the sample size of this meta-analysis was larger than previous meta-analysis.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…We believe our meta-analysis more robust than previous meta-analysis by Hu et al [20]. First, we included 2 extra studies and the sample size of this meta-analysis was larger than previous meta-analysis.…”
Section: Discussionmentioning
confidence: 90%
“…Previous meta-analysis by Hu et al indicated that IRS-2 rs1805097 polymorphism was not associated with CRC risk [ 20 ]. They only included 4 studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although, there are numerous studies that have shown the functional effects of IRS2 Gly1057Asp variation on metabolic diseases, its effect on cancer susceptibility is still controversial. Yin et al showed that IRS2 Gly1057Asp variation is associated with decreased risk of colorectal cancer while Hu et al did not observe significant connection between IRS2 Gly1057Asp variation and colorectal cancer development (Hu et al, 2014;Yin et al, 2017). These differences may due to the sample size and populations.…”
Section: Introductionmentioning
confidence: 99%